Penerapan Model Pembelajaran Talking Stick pada Pembelajaran Pendidikan Pancasila Siswa - Hanan, Hanan; Prananosa, Ahmad Gawdy; Widaswari, Dea (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to determine the completeness of the learning outcomes of Pancasila Education students in grade IV of SD Negeri 45 Lubuklinggau after applying the Talking Stick learning model. The research method used is a quasi-experiment. The population in this study is all students of class IV.B of SD Negeri 45 Lubuklinggau which is 26 students and the research sample is 26 students of class IV.B, consisting of 12 male students and 14 female students taken by random sampling. Data collection technique using t-test. Based on data analysis, the average Pre-Test score was 51.12 and the average Post-Test score was 80.38 with a significant level of a = 0.05, tcal = 4.41 and ttable 1.70, then Ha was accepted and Ho was rejected. From the results of data analysis, it can be concluded that the learning outcomes of Pancasila Education after using the Talking Stick model of grade IV students of SD Negeri 45 Lubuklinggau are significantly complete. Keywords: Talking Stick, Learning Outcomes, Pancasila Education